Carbon pillars power microbatteries. - Das, S.R.
Pillars of Power- Microscopic pillars of carbon form the electrodes in a University of California, Irvine, microbattery. Groups of pillars can be connected to the battery circuit individually so the amount of current generated can be precisely controlled.
Keywords: Anode; Cathode; Chemical reactions; Chip scale batteries; Electrodes carbon; Electrolyte ferries ion; Low current flow; Microbatteries; Semiconductor manufacturing technology; Tiny electronic gadgets